Analysis of Roland Barthes' Semiotic Theory as an Approach to Assessing Urban Fashion - Farisya Inayatullah; Deddy Wahjudi (PT Publikasiku Academic Solution, 2023)
Semiotics is a technique of studying the workings and functions of signs. The researcher analyzes Roland Barthes' semiotic approach which develops the ideas of one of the semioticians, Ferdinand de Saussure, and tries to apply the study of signs more broadly. The focus of this research is to find the meaning of a fashion phenomenon, namely urban fashion. Over time, the urban word developed as a person's lifestyle, so that the urban word was associated with fashion. In this study, the method used is qualitative. Carrying out a qualitative method system, researchers can analyze an image or photograph with Barthes' semiotic approach developed from Saussure, namely denotation, connotation and myth.